Association between Gamma-Glutamyl Transferase Levels and Pancreatobiliary Cancer Risk in Patients with Diabetes: Evidence from the National Health Insurance Cooperation Health Checkup 2009 to 2012 - Ji Hye Heo; Jun Goo Kang; Kyungdo Han; Kyong Joo Lee (Gut and Liver)
Background/Aims: Elevated gamma-glutamyl transferase (GGT) levels indicate hepatic dysfunction and have been linked to an increased risk of pancreatobiliary cancers. However, this association, particularly in individuals with diabetes mellitus (DM), requires elucidation. We aimed to examine the association between elevated serum GGT levels and pancreatobiliary cancer risk in patients with diabetes. Methods: Our study included data from the National Health Insurance Service (NHIS) database for 2,459,966 adults aged >20 years diagnosed with DM between 2009 and 2012. We examined the association between serum GGT levels and pancreatobiliary cancer risk, considering DM-related factors. Serum GGT levels were categorized into quartiles, and Cox proportional hazards analysis was performed to evaluate the association between serum GGT levels and pancreatobiliary cancer risk. Results: Over a median follow-up period of 7.2 years, 21,795 patients (0.89%) were newly diagnosed with pancreatobiliary cancer. The adjusted hazard ratio for pancreatobiliary cancer in quartiles 2-4 compared with that in quartile 1 was 1.091, 1.223, and 1.554, respectively, demonstrating a significant upward trend (p<0.001). This association remained consistent across all cancer types and was independent of the DM duration or treatment regimen. Conclusions: Elevated serum GGT levels were independently associated with an increased risk of pancreatobiliary cancer, regardless of the duration of DM or the use of oral hypoglycemic agents and insulin. While these findings suggest the potential utility of serum GGT as a biomarker for identifying individuals at higher risk of pancreatobiliary cancer within the diabetic population, further research is needed to validate its clinical applicability.